MACULAR ATROPHY FINDINGS BY OPTICAL COHERENCE TOMOGRAPHY ANGIOGRAPHY COMPARED WITH FUNDUS AUTOFLUORESCENCE IN TREATED EXUDATIVE AGE-RELATED MACULAR DEGENERATION. Issue 2 (February 2019) - Takasago, Yukari; Shiragami, Chieko; Kobayashi, Mamoru; Osaka, Rie; Ono, Aoi; Yamashita, Ayana; Tsujikawa, Akitaka; Hirooka, Kazuyuki
Abstract : Purpose: To compare the areas of choriocapillaris (CC) nonperfusion and macular atrophy (MA) in treated exudative age-related macular degeneration. Methods: This was a prospective, observational, cross-sectional study. Forty-four eyes exhibiting MA (42 patients with age-related macular degeneration), with a dry macula, underwent fundus autofluorescence and optical coherence tomography angiography. The area of MA detected by fundus autofluorescence and CC nonperfusion detected by optical coherence tomography angiography was measured using image analysis software. The rates of concordance between the MA and CC nonperfusion areas were calculated. We qualitatively and quantitatively compared the areas of MA and CC nonperfusion in age-related macular degeneration eyes. Results: The mean areas of MA and CC nonperfusion were 5.95 ± 4.50 mm 2 and 10.66 ± 7.05 mm 2, respectively (paired t -test, P < 0.001). In 39 eyes (88.6%), the CC nonperfusion area was larger than the MA area, and the mean CC nonperfusion area was significantly larger than the mean MA area. Fundus autofluorescence matching optical coherence tomography angiography showed that the CC nonperfusion area was almost included in the MA area. The mean concordance rate for the MA area inside the CC nonperfusion area was 87.7 ± 13.9%. Conclusion: The MA and CC nonperfusion areas markedly overlapped. The area of CC nonperfusion correlated with the MA area. Choroidal ischemia might be involved in the pathogenesis of MA in treated age-related macular degeneration. Abstract : The area of choriocapillaris nonperfusion on optical coherence tomography angiography correlated with the area of macular atrophy on fundus autofluorescence in eyes with exudative age-related macular degeneration. Choroidal ischemia might be involved in macular atrophy in treated age-related macular degeneration.